2008
DOI: 10.1038/jcbfm.2008.129
|View full text |Cite
|
Sign up to set email alerts
|

Transient Widespread Blood—Brain Barrier Alterations after Cerebral Photothrombosis as Revealed by Gadofluorine M-Enhanced Magnetic Resonance Imaging

Abstract: Magnetic resonance imaging (MRI) is a powerful tool to assess brain lesions, but currently available contrast agents are limited in the assessment of cellular and functional alterations. By use of the novel MRI contrast agent gadofluorine M (Gf) we report on imaging of transient and widespread changes of blood-brain barrier (BBB) properties as a consequence of focal photothrombotic brain lesions in rats. After i.v. application, Gf led to bright contrast in the lesions, but also the entire ipsilateral cortex on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 44 publications
(75 reference statements)
5
57
0
1
Order By: Relevance
“…58 The same agent has been used in a model of ischaemic stroke to demonstrate widespread transient increases in BBB breakdown. 59 Another study showed changes in the circumventricular organs during EAE, which the authors correlated with disease severity and onset. 60 Another study found no changes in Gf enhancement after intraperitoneal injection of LPS.…”
Section: Endothelial Activationmentioning
confidence: 98%
“…58 The same agent has been used in a model of ischaemic stroke to demonstrate widespread transient increases in BBB breakdown. 59 Another study showed changes in the circumventricular organs during EAE, which the authors correlated with disease severity and onset. 60 Another study found no changes in Gf enhancement after intraperitoneal injection of LPS.…”
Section: Endothelial Activationmentioning
confidence: 98%
“…Consistent with previous studies, macroscopic sections confirmed BBB breakdown in most layers of the cortex surrounding the lesion core ( Figure 1A, bottom). 8,28,29 Cellular damage was detected in the peri-ischemic region using intravital microscopy after intravenous injection of either PI or binding annexin A5, while nonbinding annexin A5 gave no specific staining ( Figure 1B). Positive annexin A5 staining, while generally colocalized with PI (n = 4), was most prominent in close proximity to blood vessels, mainly venules.…”
Section: Modelmentioning
confidence: 99%
“…Such leukocyte trafficking is probably a key event in the pathophysiology of MS [Bahbouhi et al, 2009;Kerfoot and Kubes, 2002] that contributes to the localized breakdown of the BCNSB. Both gadolinium diethylenetriaminepenta-acetate (Gd-DTPA)-and iron oxideenhanced MRI has indicated BCNSB breakdown in MS as well as in an experimental model of MS: EAE [Stoll et al, 2009] and postmortem MRI indicate alterations in both focal and diffuse BCNSB abnormalities in subjects with MS [Vos et al, 2005]. There is also evidence to indicate that dynamic contrastenhanced MRI is able to detect subtle blood-brain barrier leakage in visibly non-enhancing MRI lesions in MS [Soon et al, 2007].…”
Section: Cd25mentioning
confidence: 93%